Harold & Hog pretend for real! - Willems, Mo 1968-; Santat, Dan 1975- (Hyperion Books for Children, an imprint of Disney Book Group, 2019)
Can the friendship of best friends Harold and Hog, a carefree elephant and a careful hog, survive a game of pretending to be Mo Willems's Elephant and Piggie?
Keywords: Best friends / Juvenile fiction; Friendship / Juvenile fiction; Imagination / Juvenile fiction; Best friends / Fiction; Friendship / Fiction; Imagination / Fiction; Characters in literature / Fiction; Humorous stories; JUVENILE FICTION / Animals / Elephants; JUVENILE FICTION / Animals / Pigs; JUVENILE FICTION / Humorous Stories; Best friends; Friendship; Imagination; Children's stories; Readers; Fiction; Juvenile works; Humorous fiction; Animal fiction; Comic; Bilderbuch